+0  
 
+1
46
1
avatar+172 

Compute \(cos (A-90) + 1 = 2(cos A)\)

 May 3, 2020
 #1
avatar+111326 
+2

cos (A -90)  + 1  = 2(cosA)

 

cosA cos90  + sinAsin90 + 1  = 2cosA

 

sinA  + 1  =  2 cos A       square both sides

 

sin^2 A  + 2sin A  + 1  =  4cos^2 A

 

sin^2A + 2sin A  + 1  =  4 ( 1 - sin^2A)

 

sin^2A  + 2sin A  + 1  =  4 - 4sin^2     rearrange as

 

5sin^2A  + 2sinA - 3   =  0

 

(5sin A - 3) ( sin A + 1)  =  0

 

5sin A  - 3  = 0      or           sin A  = -1      A  = 3pi/2      cos (3pi/2)   = 0 

sin A  = 3/5

 

so cos A =4/5        or      cos A   = 0

 

Proof

 

sin A + 1  = 2cosA               sin A + 1  = 2cosA     

3/5 + 1 = 2(4/5)                      -1   +  1  = 2(0)

3/5 + 5/5  = 8/5                            0  =  0

     8/5  = 8/5

 

 

cool cool cool

 May 3, 2020

16 Online Users

avatar